Effects of Glycyrrhiza glabra Root extract On Some Physiological Parameters in albino male rats treatment with lead acetate - Rasha Shamil Hussein; Sura Saad AbulAzeez (Tikrit Journal of Pure Science, 2023)
The present study used 20 albino rats that distributed randomly to five groups (each group contain 4 rats), the first group was control group administrated only normal diet and water, the second group administrated with lead-acetate for four weeks, the third group administrated with lead-acetate for six weeks, the fourth group administrated with lead-acetate for four weeks and then, treated with 1ml root extract for 15 days, the fifth group administrated with lead-acetate for six weeks and then, treated with 1ml root extract for 15 days. The ALT, AST, ALP, bilirubin and creatinine levels were increased while albumin levels were decreased and showed high significant changes (P < 0.01) in groups that administrated with lead-acetate compared with control group, but the levels of all parameters back to normal when the groups that administrated with lead-acetate treated with Glycyrrhiza glabra  root extract. It was concluded from this study that roots extract has amply good effect on liver and kidneys enzymes.